(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
The paper presents a technical solution for monitoring and operating the antihail missile launchpad using an internet-connected wireless remote control, which operates in the 433 MHz ISM frequency band. A small-size experimental model of the real launchpad was devised and built, to test the local operation of the remote control and its over-the-internet monitoring function. When designing the experimental model, attention was given to preserving the characteristics of the actual launchpad,such that after testing the technical solutions of the remote control on the model, they could be implemented on the real launchpad with minimal modifications. This experimental model can also be used for staff training during the active off-season. The proposed technical solution presents an example of how the electrical machine, seen as an element of execution, is included in the concept of the Internet of Things.